ASSESSING THE IMPACTS OF INDUSTRIAL GROWTH ON AIR QUALITY THROUGH GEOSPATIAL TECHNIQUES: A CASE STUDY OF LAHORE (Pakistan Journal of Science, 2025)
Air quality is the new focus in atmospheric sciences. The number of gases and pollutants in the air determines its air quality. The major source of these gases and pollutants in the atmosphere are many anthropogenic activities but this research is based on industries. The study area of this research is Lahore as it is the 2nd largest city of Pakistan and has a wide variety of polluting industries such as chemical, agriculture, technology, fuel, steel and iron, fashion, food-retail and construction. For this purpose, 10-meter satellite images Sentinel-5p and Sentinel 2A from EO Browser and USGS Earth Explorer, respectively, used to collect the air quality and LULC data. Following parameters were analysed: Aerosol Index (AI), CO, HCHO, O3, NO2 and CH4. The data was then processed in ArcGIS 10.5 by using geo-spatial techniques such as Interpolation (IDW) and Weighted Sum. IDW was applied to determine the abundance of above parameters and Weighted Sum was applied to determine the UAQI of Lahore. Moreover, Point Density was applied on industrial data to check its influence on air quality. Results showed that the air quality of Lahore is affected badly in the areas where the ratio of industries is high. UAQI of Ganj Baksh and Gulberg lie in very bad category due to the incidence of numerous industries in these areas.
Keywords: Air quality; Sentinel-5p; Urban Air Quality Index (UAQI); geo-spatial techniques